Exploring the Mediating Effect of Engagement on the Relationship Between Psychological Capital and Service-Learning Effectiveness - Tung-Miao Chang; Kai-Yun Chang (Journal of Educational Practice and Research, 2024)
Psychological capital, which originated from positive psychology, can improve learning outcomes, with engagement playing a key role. The purpose of this study is to explore the relationship between university students’ psychological capital, engagement, and service-learning effectiveness, and to test the mediating effect of engagement. The study utilized a survey research method, targeting service-learning students from both public and private universities in southern Taiwan. Data were collected from 412 university students, and Structural Equation Modeling (SEM) was used to analyze the data. The results showed that psychological capital did not have a direct effect on service-learning effectiveness. However, psychological capital had a significant direct effect on engagement, and engagement had a significant direct effect on service-learning effectiveness. Furthermore, engagement fully mediated the relationship between psychological capital and service-learning effectiveness. Thus, it is essential to further promote psychological capital and strengthen engagement among university students to enhance service-learning effectiveness in practice. Based on these results, this study offers several implications for educational practice and provides relevant suggestions for future research.